USE OF DIGITAL TECHNOLOGIES IN INCREASING THE COGNITIVE ACTIVITY OF STUDENTS IN THE MODERN EDUCATION SYSTEM - Xusniddin Muhiddinovich Ashurov (European Science Publishing, 2024)
In this article, the actual aspects and importance of the use of digital technologies in education are highlighted on a theoretical basis, and the necessary recommendations are given. In the article, the priority directions for the development of the educational process based on the use of digital technologies in the higher education system of our republic and the analysis of their possibilities are defined. Also, proposals are presented on the implementation of the existing opportunities for improving the professional pedagogical skills of teachers based on the introduction of digital technologies in higher education.
Keywords: digital technology, digital education, pedagogical skill, task, efficiency, education, personnel, information and communication technologies, cognitive activity.